The method of the internet authorization for the protection of shareware programs - Андрущенко, Дмитрий Михайлович; Козина, Галина Леонидовна (Eastern-European Journal of Enterprise Technologies, 2014)
The possibility of providing users with a shareware version of the program is promising for software developers. In this case, the user may use a fully working version for a limited period, or only part of the program functions, but without time limitation. However, this possibility is often a weak point in the software protection. There are many cases of unauthorized use of shareware programs. The authors have developed a software protection protocol, including shareware programs, which is based on using the electronic digital signature mechanism. In developing the program, its paid features are placed in a separate dynamic-link library DLL. The original file of the library is stored only on a remote server and is not distributed with the program upon its purchase. The file is loaded into the program memory at the time of its launch by the authorization over the Internet. Description of the protocol of data transfer between the program and the remote server, as well as the method of the paid functional protection in the software, is given in the paper. In addition, the software implementation of the protocol was executed and, on its basis, the computer program protection module was developed. This method in contrast to the existing allows a developer easily distribute software through the Internet without the worry about the possible appearance of illegal copies. Developer has the opportunity to monitor the process of using the licenses provided, reveal offenses and block licenses. The server part allows to "follow" the user’s actions such as starting a program, creating a new document, using the data handler, generating a report, etc. and block the program in case of unauthorized use. Providing licenses over the Internet allows the user quickly renew the license or replace one license with another.